Atlas of cardiac endothelial cell enhancer elements linking the mineralocorticoid receptor to pathological gene expression - Deng, Lisa; Pollmeier, Luisa; Bednarz, Rebecca; Cao, Can; Laurette, Patrick; Wirth, Luisa; Mamazhakypov, Argen; Bode, Christine; Hein, Lutz; Gilsbach, Ralf; Lother, Achim (Science advances, 2024)
Endothelial cells play crucial roles in physiology and are increasingly recognized as therapeutic targets in cardiovascular disease. Here, we analyzed the regulatory landscape of cardiac endothelial cells by assessing chromatin accessibility, histone modifications, and 3D chromatin organization and confirmed the functional relevance of enhancer-promoter interactions by CRISPRi-mediated enhancer silencing. We used this dataset to explore mechanisms of transcriptional regulation in cardiovascular disease and compared six different experimental models of heart failure, hypertension, or diabetes. Enhancers that regulate gene expression in diseased endothelial cells were enriched with binding sites for a distinct set of transcription factors, including the mineralocorticoid receptor (MR), a known drug target in heart failure and hypertension. For proof of concept, we applied endothelial cell-specific MR deletion in mice to confirm MR-dependent gene expression and predicted direct MR target genes. Overall, we have compiled here a comprehensive atlas of cardiac endothelial cell enhancer elements that provides insight into the role of transcription factors in cardiovascular disease.